INTERAKSI SIMBOLIK PADA KOMUNITAS PEMBELA BINATANG INDONESIA - Wiratri Anindhita; Valencia Chretella (Jurnal Komunikasi dan Bisnis, 2019)
Animal Defenders Indonesia Community is a pro-animal community that was formed in 2011 and has previously conducted similar activities but sporadically and uncoordinated or in groups. Animal Defenders Indonesia managed by Doni Herdaru Tona is oriented to several things such as rescue, rehab, rehome, and educational program. Researchers wanted to illustrate how symbolic interactions took place between the founder and the animals and between the volunteers and the animals in that place. The theory used is the theory of symbolic interaction with the support of community concepts and life experiences. Currently, research on a community has been very frequent, but researchers are taking a wildlife protection community that is still rarely found to research. The results obtained by the researchers are that the researchers describe how the reality of symbolic interaction that occurs between humans and animals is clearly evident in this study that the dogs in this film are treated like a family itself not as a pet only.Keywords: Community, Animal, Symbolic Interaction, Founder, Volunteer.